2014
DOI: 10.1002/jmri.24696
|View full text |Cite
|
Sign up to set email alerts
|

Computer‐automated focus lateralization of temporal lobe epilepsy using fMRI

Abstract: Purpose To compare the performance of computer-automated diagnosis using fMRI interictal graph theory (CADFIG) to that achieved in standard clinical practice with MRI, for lateralizing the affected hemisphere in temporal lobe epilepsy (TLE). Materials and Methods Interictal resting state fMRI and high-resolution MRI were performed on 14 left and 10 right TLE patients. Functional topology measures were calculated from fMRI using graph theory, and used to lateralize the epileptogenic hemisphere using quadratic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 19 publications
1
24
1
Order By: Relevance
“…These results were comparable to those of previous studies that used machine learning approaches for volumetry, DTI, and fMRI. [2][3][4][5] Although our results for classification accuracy do not exceed those of previous reports that applied machine learning to DTI using voxel-based approaches 3 or a fractional anisotropy (FA) skeleton generated by tract-based spatial statistics (TBSS), 4 the graph-based approach has considerable strengths as follows. First, it is directed to the recent trend to consider diseases of the brain as network disorders.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…These results were comparable to those of previous studies that used machine learning approaches for volumetry, DTI, and fMRI. [2][3][4][5] Although our results for classification accuracy do not exceed those of previous reports that applied machine learning to DTI using voxel-based approaches 3 or a fractional anisotropy (FA) skeleton generated by tract-based spatial statistics (TBSS), 4 the graph-based approach has considerable strengths as follows. First, it is directed to the recent trend to consider diseases of the brain as network disorders.…”
Section: Discussioncontrasting
confidence: 53%
“…To increase the certainty of lateralization of the epileptogenic focus and obviate the need for invasive intracranial electrode placement, prior studies have investigated the utility of quantitative or automated MR image analyses, including voxelbased morphometry, 2,3 diffusion tensor imaging (DTI), 3,4 and functional MR imaging (fMRI). 5 DTI can approximate the white matter architecture by describing the directionality and magnitude of water diffusion. In TLE, the decrease in fractional anisotropy (FA) tends to be maximal at the epileptic zone and subtle at a distance, 6 and decreased FA in the extra-temporal regions as well as within the ipsilateral temporal lobe suggests that the network is altered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher level of temporal stationarity of betweenness centrality may lead to a higher level of sensitivity in characterizing hub distributions based on static analytic approaches. Betweenness centrality has been consistently implicated in both localizing [7] and lateralizing TLE [61, 62], whereas eigenvector centrality has been less well implicated.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Additionally, some have applied these methods to EEG readings to automate seizure detection and localize epileptogenic focus. 10,11 In the field of neuro-oncology, machine and deep-learning approaches have been used to analyze magnetic resonance images to classify and grade tumors, and predict survival. [12][13][14] These are only some of the applications of Big Data methods that are currently under investigation in neurosurgery, and specifically by our group at the Computational Neuroscience Outcomes Center, and a more in depth review can be found elsewhere.…”
mentioning
confidence: 99%